Open Source Search Analytics - Elasticsearch (2018)
“Centralize, Transform & Stash Your Data”, Logstash is an open source, server-side data processing pipeline that ,ingests data from a multitude of sources simultaneously, transforms it, and then sends it to your favorite “storage” (Ours is Elasticsearch,naturally, but there are more options), “The Heart of the Elastic Stack”, ?Search server based on Lucene (API - Free and open-source information retrieval software library), Written in Java with Apache license, Elasticsearch is a distributed, RESTful search and analytics engine capable of solving a growing number of use cases. As the heart of the Elastic Stack, it centrally stores your data so “you can discover the expected and uncover the unexpected”.